tDCS Stimulation of the dlPFC Selectively Moderates the Detrimental Impact of Emotion on Analytical Reasoning - Trémolière, Bastien; Maheux-Caron, Véronique; Lepage, Jean-François; Blanchette, Isabelle (Frontiers in Psychology, 2018)
There is evidence of a detrimental effect of emotion on reasoning. Recent studies suggest that this relationship is mediated by working memory, a function closely associated with the dorsolateral prefrontal cortex (dlPFC). Relying on transcranial direct current stimulation (tDCS), the present research explores the possibility that anodal stimulation of the dlPFC has the potential to prevent the effect of emotion on analytical reasoning. Thirty-four participants took part in a lab experiment and were tested twice: one session using offline anodal stimulation (with a 2mA current stimulation applied to the left dlPFC for 20 minutes), one session using a control (sham) stimulation. In each session, participants solved syllogistic reasoning problems featuring neutral and emotionally negative contents. Results showed that anodal stimulation diminished the deleterious effect of emotion on syllogistic reasoning, but only for a subclass of problems: problems where the conclusion was logically valid. We discuss our results in the light of the reasoning literature as well as the apparent variability of tDCS effects.